Turbine design effect to the speed of turbine and output voltage of the Pico-Hydropower generator system - Haziq Irfan, Hamdan (2021)
This report deals with the study on the turbine design effect on the performance of pico hydropower generator system in flowing water. The objective of this study is to design an easily installed and low costs Pico-Hydropower system for houses water tank to supply power for daily consumption. The objective of this project also is to test the type and capacity of loads to be supplied by the pico-hydropower and to study the performance of the developed Pico-Hydropower system in terms of Power (W), Voltage (V) and Current (A). The experiment was conducted by using the Pelton turbine and Turgo turbine printed by 3D-printer and choose which is most efficiency for this system. The potential energy created by the stream of the water is converted to mechanical energy and the mechanical energy will rotate the blade of the turbine. As the blade of the turbine is rotated, the magnetic field inside the generator been cut and the induction of electrical will happen. As the result, the electrical power is produced by the turbine. All the electrical power that produced of this project that Pico-Hydro power generator system will charge the battery or power bank. The obtained result shows that the value of flow rate affect the power generated by the turbine. The value of power generated by the turbine increase as the flow rate increase. The result also indicates that difference value of the voltage will generate difference power. The power generated by turbine is depends on the flow rate because the high flow rate will create enough energy to rotate the blade of the turbine and at the same time the electrical power is produced.